Nephroprotective Activity of Marrubiin against Cisplatin-induced Nephrotoxicity in Albino Male Wistar Rats - Zhang, Guanglu; Chen, Yan; An, Huiliu; Hao, Nan; Shi, Haitao (Indian Journal of Pharmaceutical Education and Research, 2024)
Background One of the most effective anti-cancer medications used to treat various cancers is Cisplatin (CP). Due to its nephrotoxicity, its usage is restricted. The purpose of this investigation is to assess Marrubiin’s influence in the protection of rats against CP nephrotoxicity. Materials and Methods Animals were divided into five groups. The body weight and kidney weight were measured for all the experimental groups. Urine output and blood samples were collected to assess the Blood Urea Nitrogen (BUN) and Creatinine (Cr) present in the experimental animals. Furthermore, the oxidative stress markers, antioxidant enzymes, inflammatory markers and histopathological studies were carried out to assess the impact of Marrubiin treatment in a dose-dependent manner. Results We observed that treating animals CP-induced animals with Marrubiin aided in improving kidney function. Marrubiin significantly increased the level of antioxidant enzymes, histopathology conditions and body weight of the animals. It also downregulated the inflammatory markers, levels of BUN and Cr, urine output, kidney weight and oxidative stress markers. Conclusion Thus, we conclude that Marrubiin can be used to protect the kidney from injury induced by cisplatin treatment.
Keywords: Cisplatin; Marrubiin; Nephrotoxicity; Oxidative marker